(untitled) (World Bulletin of Management and Law, 2025)
The article examines international and national legal instruments regulating the individual’s right to access and receive information, providing a concise analysis of their content. The right to information is recognized as an integral part of fundamental human rights. In contemporary legal scholarship, the study of this right and its role within the broader framework of information law is relatively new and is gradually securing its position in national legislation. The analysis demonstrates that ensuring the individual’s right to obtain information carries significant value for the effective realization and protection of human rights.